Interplay Between Silicon Nanocrystal Size and Local Environment Within Porous Silicon on the Analyte-Dependent Photoluminescence Response. Issue 10 (October 2019) - Matthews, Samantha; Bright, Frank V.
Porous silicon (pSi) exhibits strong photoluminescence (PL) and its PL is often exploited for chemical sensor development. However, the sensor response is not uniform across a pSi specimen. We use co-localized confocal PL and Raman scattering mapping to establish a relationship between the analyte-induced PL response and the silicon nanocrystallite size, size distribution, and amorphous silicon (aSi) contribution across a pSi specimen. Using toluene as a model analyte, high analyte-induced PL response is associated with areas within the specimen that have (i) low aSi content, (ii) silicon nanocrystallites having diameters between 2 and 5 nm, and (iii) silicon nanocrystallites that exhibit a narrow size distributions (≤1% relative standard deviation).